Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Đặng Ngọc Nghĩa (Số: 12126/BCT-KH) - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Đặng Ngọc Nghĩa (Số: 12126/BCT-KH) ngày 16/12/2016